Geotechnical data bank for Bangkok subsoil conditions/GIS system - Ronakit Chinkulkijniwat; Balasubramaniam, A.S.; Lin, Der Guey; Shibuya, S.; Noppadol Phien-Wej; Asian Institute of Technology Partial Scholarship (Bangkok : Asian Institute of Technology, 1998)
A geographic information system (GIS)-based program for developing subsurface profiles in central pait of Bangkok area from a series of collected borehole is presented. Any number of cross-section profile can be generated and viewed interactively. Then subsurface profiles, generated by this program, are discussed. The procedures of calcuiation are programmed in Microsoft Visual Basic language using WINDOW'95 system. The database system for geotechnical data in Bangkok area is also established. Microsoft Access is used as database management in this study. By using database engine, the geotechnical data of a specific borehole can be retrieved and shown on the screen both in numerical and graphical fo1mat.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology
Keywords: Geographic information systems; Underground areas -- Thailand -- Bangkok